The impact of injury on career progression in elite youth football: findings at 10 years - Bangert, Yannic; Jaber, Ayham; Trefzer, Raphael; Zietzschmann, Severin; Koch, Kevin-Arno; Kern, Ralph; Spielmann, Jan; Renkawitz, Tobias; Weishorn, Johannes (Journal of Clinical Medicine, 2024)
Background: There is a lack of evidence regarding the impact of time loss, match exposure, and age at injury on career progression in elite football. Therefore, the aim of this study was to identify injury characteristics and their influence on career progression in a German youth academy. Methods: During the 2012/2013 season, a prospective cohort study reported 107 time-loss injuries among 130 young athletes from an elite German soccer academy. Individual career progression was analyzed using 10-year data. Results: Injuries and time loss were not associated with career progression (p > 0.05) in the overall cohort. In the U17 and U19 groups, 24% were able to reach the professional level, with injuries significantly decreasing this probability (p = 0.002). Injuries lasting more than 28 days had a negative impact on career progression compared to minor injuries (30% vs. 10%; p = 0.02). Conclusions: Not only the characteristics of injuries, but also their impact on career development, vary with age. In the U17 and U19 age groups, serious injuries resulting in more than 28 days of absence have a negative impact on career progression. It is important to be aware of these effects in order to focus on the prevention of long-term injuries to ensure the optimal development of young athletes.